Uses of multimodal statements on the playground: a Foucaultian approach to multimodal discourse analysis. Issue 2 (15th March 2018) - Ranker, Jason
ABSTRACT: In this study, I draw upon the concept of a statement (l'énoncé), Foucault's fundamental discursive unit, as developed in The Archaeology of Knowledge, extending and applying the concept to a group of children's multimodal discourse operations on the playground, and thereby developing the concept of a multimodal statement . I do this by focusing on Foucault's semiotic grounding of the statement, which he describes as being constituted by a group of signs. My analytical approach involved developing a form of multimodal transcription that enabled the isolation of individual multimodal statements within a focal discursive event. In later stages of analysis, I identified the signifiers (from across multiple modes) that comprised the students' multimodal statements, and found that these multimodal statements were discursive practices that created a network of nodal point signifiers drawn from multiple modes. Through these multimodal discourse processes, the students created subjective positions as part of a local discursive formation, which I refer to as a multimodal discursive microformation : a social semiotic web of subjectification that the children produced.